UNFAVORABLE EFFECT OF MENTAL STRESS IN ARTHUR DIMMESDALE'S ROLE AS A PRIEST IN NATHANIEL HAWTHORNE'S NOVEL THE SCARLET LETTER (1986) ; A PSYCHOANALYTIC APPROACH - SAPTARINI, APRILIANA DEWI (2011)
The subject of this research is how unfavorable effect of mental stress for Arthur Dimmesdale, as the role of a priest in Nathaniel Hawthorne's novel The Scarlet Letter. It was viewed from psychoanalytic approach. The objective of the research paper is analyzing the effect of repressed desire based on psychoanalytic theory by identifying the personality of major and minor character and structural elements of the novel. Achieving the object of this research, the writer uses library research to gain the accurate data in creating a valid and accountable research. The application of this method is by scrutinizing library materials which have strong relation with the problem examined in this writing. There are two types of the data including main data and supporting data. In assessing the research, the writer uses structural analysis approach through the theories to clarify the intrinsic elements. Furthermore, to analyze the personality of Arthur Dimmesdale. The writer applies psychoanalytic theory which discusses the process and outcome of the repressed of emotion and someone's biological desire. The result of this research shows that human emotion and desire which can not be repressed completely lost and it will cause the nature of certain character that makes up a new personality. By new Arthur Dimmesdale's personality, it can be seen in his actions in public society.